Metrics for comprehensive monitoring that assess the performance of cross-country skiers in sprint races - Salova Yu. P.; Lenkova S. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the usefulness of step-by-step integrated monitoring metrics in forecasting performance in ski sprints, using the outcomes of the Russian Cup 2023-2024 as a case study.